Verbal, non-verbal and phenomenal consciousness: proposing a conceptual extension on radical behaviorism. (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
From the perspective of radical behaviorism, consciousness, or “conscious behavior”, is defined as the discriminative responding to one’s own behavior. In the present paper it is proposed a definition of consciousness that extends beyond its verbal domain. Moreover, it is suggested that a third definition of consciousness, based on philosophy of mind, in which the term indicates the subjective character of behavior, is compatible with radical behavioristic philosophy. Thus, there would be three definitions of consciousness: verbal, non-verbal and phenomenal. Extending the concept of consciousness without violating radical behavioristic principles is important because it puts radical behaviorism in the core of contemporary discussions of philosophy of mind and neurosciences regarding consciousness.
Keywords: radical behaviorism; Skinner; consciousness; experience; subjectivity